2018
DOI: 10.1111/jfpp.13814
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of structure and cooking quality of brown rice using ultrasonic and enzymatic treatments

Abstract: Brown rice (Oryza sativa L.) was subjected to ultrasonic treatment (UT) and three enzymatic treatments (ET) with cellulase, glucoamylase and α‐amylase. All treatments changed pasting properties of brown rice flour and structure of brown rice grain surface, but only UT and α‐amylase treatment (AT) significantly affected starch granules inside the grain. During cooking, water uptake and volume expansion of UT brown rice were higher than those of ET. Both UT and ET decreased hardness of the cooked brown rice from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Similar observations were reported by Zhang et al [51] ; the enhanced water absorption of UT brown rice effectively decreased from 28.7 mins to 24.3 mins with enzymatic treatment only and further reduced to 22.3 mins with ultrasonic and enzymatic treatments. Moreover, an increase in water uptake of UT Thai brown rice [84] , [73] reduced the cooking time of Shanlan rice after UT [88] . Volume expansion is also affected by ultrasonication; Dang et al [73] reported an increase in volume expansion ratio of brown rice (2.83 ± 0.24 to 3.33 ± 0.00) after ultrasonication.…”
Section: Application Of Ultrasonic Treatment On Rice Grain To Enhancementioning
confidence: 97%
See 2 more Smart Citations
“…Similar observations were reported by Zhang et al [51] ; the enhanced water absorption of UT brown rice effectively decreased from 28.7 mins to 24.3 mins with enzymatic treatment only and further reduced to 22.3 mins with ultrasonic and enzymatic treatments. Moreover, an increase in water uptake of UT Thai brown rice [84] , [73] reduced the cooking time of Shanlan rice after UT [88] . Volume expansion is also affected by ultrasonication; Dang et al [73] reported an increase in volume expansion ratio of brown rice (2.83 ± 0.24 to 3.33 ± 0.00) after ultrasonication.…”
Section: Application Of Ultrasonic Treatment On Rice Grain To Enhancementioning
confidence: 97%
“…(A, C) Brown rice; (B, D) milled rice. Sonication conditions: (a) 40 kHz, 150 W, 30 mins, 30 °C [84] ; (b) 40 kHz, 300 W, 10 mins, 4 °C [53] ; (c) 16 kHz, 2 kW, 30 mins, 55 °C [50] ; (d) 53 kHz, 5 mins, 55 °C [52] . Reprinted with permission.…”
Section: Changes In Physicochemical Properties Of Ultrasonicated Ricementioning
confidence: 99%
See 1 more Smart Citation
“…The major loss in these chemical components could be caused by the soaking of brown rice in water and buffer solution during ultrasonic and ETs. Amylose content was reported in Dang et al (). Amylose content was reduced significantly in case of GT and AT, due to the starch hydrolysis action of these enzymes.…”
Section: Resultsmentioning
confidence: 86%
“…The major loss in these chemical components could be caused by the soaking of brown rice in water and buffer solution during ultrasonic and ETs. Amylose content was reported inDang et al (2018).…”
mentioning
confidence: 99%